P-modified hollow carbon mesoporous nanospheres decorated with ultrafine OsP alloy nanoparticles for nonacidic hydrogen evolution. Issue 24 (9th June 2022) - Liu, Min; Shi, Keke; Duan, Zhongyao; Zhang, Mei; Xu, You; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : OsP/PHMCSs-600 exhibits excellent electrocatalytic activity and stability toward the hydrogen evolution reaction under alkaline and neutral conditions. Abstract : The nonacidic hydrogen evolution reaction (HER) holds great promise for the generation of hydrogen and the key factor is the development of highly effective electrocatalysts with large surface area, abundant exposed active sites, and superior electron conductivity. P-modified hollow mesoporous carbon spheres decorated with OsP alloy nanoparticles (OsP/PHMCSs) are synthesised using a combination of a hard template and subsequent pyrolysis methods and tested for the HER under alkaline and neutral conditions. The HER activity of OsP/PHMCSs outperforms that of commercial Pt/C, with overpotentials of only 15 mV and 56 mV at a cathodic current density of 10 mA cm −2 in alkaline and neutral media, respectively, due to their unique structure and optimized composition. The hybrid nanoarchitecture encapsulating highly active nanoparticles in mesoporous conductive supports provides a promising approach for developing Os-based electrocatalysts with high activity and stability.